A Typology of ICU Patients and Families from the Clinician Perspective: Toward Improving Communication. Issue 6 (3rd June 2017) - Leslie, Myles; Paradis, Elise; Gropper, Michael A.; Milic, Michelle M.; Kitto, Simon; Reeves, Scott; Pronovost, Peter
ABSTRACT: This paper presents an exploratory case study of clinician–patient communications in a specific clinical environment. It describes how intensive care unit (ICU) clinicians' technical and social categorizations of patients and families shape the flow of communication in these acute care settings. Drawing on evidence from a year-long ethnographic study of four ICUs, we develop a typology of patients and families as viewed by the clinicians who care for them. Each type, or category, of patient is associated with differing communication strategies, with compliant patients and families engaged in greater depth. In an era that prioritizes patient engagement through communication for all patients, our findings suggest that ICU teams need to develop new strategies for engaging and communicating with not just compliant patients and families, but those who are difficult as well. We discuss innovative methods for developing such strategies.